A new design of cable anchor for ultra-high fatigue stress cable net of largest telescope in the world. (February 2021) - Zhu, Wanxu; Jia, Kefei; Fu, Feng; Lan, Dongqiu; Qian, Kai
Abstract: As the largest filled-aperture radio telescope in the world, China's five-hundred-meter diameter Aperture Spherical Radio Telescope (FAST) is supported using a unique ultra-high fatigue stress cable net structure to enable flexible deformation of the reflector. As each of the supporting cables is required to be capable of bearing an ultra-high fatigue stress (up to approximately 500 MPa), a new type of cable anchor is specially designed in this paper to provide required high prestress level in the cables. In this paper, the stress distribution of the steel strands inside the chilled cast anchor is analyzed, a method for adjusting the prestress force of the cable anchor is developed which can effectively reduce the stress concentration of the steel strands inside chilled cast anchor. The relationship between the anchorage efficiency coefficient and its influencing factors is established, which can be used for the design of the anchor and to optimize the performance of cable anchorage. Highlights: A method to reduce the stress concentration of the steel strands inside chilled cast anchor is proposed. The mathematical relationship between the anchorage efficiency coefficient and its influencing factors is established. A innovative double-cone cable anchor consisting of a main anchor cup and an auxiliary anchor cup is proposed.